The Flavonoids, Phenolics, and Antioxidant Activity from Ethanol Extract of Fibraurea tinctoria Lour - Fathiah, Fathiah; Purwaningsih, Indah; Suryana, Budi (JURNAL INFO KESEHATAN, 2024)
Oxidative stress has long been associated with increased risk for several diseases. Antioxidant is a molecule that inhibits the oxidation of other molecules and delays or prevents oxidative damage. Natural phenolic and flavonoid compounds are plant secondary metabolites directly contributing to antioxidant activity. Fibraurea tinctoria Lour, often called the yellow root, is a plant that has long been known in the traditional medicine of the native tribes of West Kalimantan to treat several diseases, including malaria, jaundice, and diabetes. This study aimed to quantify the total phenolic (TPC) and flavonoid (TFC) contents and antioxidant activity of the ethanol extract of yellow root stems. Yellow root stems were extracted by maceration in 96% ethanol for four days. The total phenolic, flavonoid, and antioxidant activities were measured using the Folin-Ciocalteu, AlCl3, and DPPH methods. Phytochemical screening showed that the ethanol extract of yellow root stems contains phenolics, flavonoids, alkaloids, saponins, tannins, and steroids/triterpenoids. The total phenol and flavonoid contents were 40.2 mg GAE/g extract and 61.2 mg QE/g extract, respectively. The ethanol extract of yellow root stems showed moderate DPPH scavenging activity, with an IC50 of 152.13 ppm. From this study, it can be concluded that this plant could be a potential source of natural antioxidants.